2007
DOI: 10.1074/jbc.m608666200
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Differential Modulation of Immune Responses by Hsp60 and Lipopolysaccharide

Abstract: Activation of professional antigen-presenting cells (APC) is Activation of antigen-presenting cells (APC)2 such as dendritic cells (DC) and macrophages is a critical step in the initiation of innate as well as adaptive immune responses and is known to be induced by pathogen-associated molecular pattern (PAMP) molecules such as bacterial lipopolysaccharide (LPS) and other endotoxins. These molecules are recognized by pattern recognition receptors (PRR) like members of the conserved Toll-like receptor (TLR) fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 53 publications
(69 reference statements)
5
88
0
2
Order By: Relevance
“…A new role has emerged for large HSP as endogenous danger signals which augment the induction of innate and adaptive immunity through interaction with TLR [6,7,9]. In contrast, our data suggest a novel role for HSP-27 as an MO anti-danger signal down-modulating innate and adaptive immunity similar to the role suggested for CD200 [49].…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…A new role has emerged for large HSP as endogenous danger signals which augment the induction of innate and adaptive immunity through interaction with TLR [6,7,9]. In contrast, our data suggest a novel role for HSP-27 as an MO anti-danger signal down-modulating innate and adaptive immunity similar to the role suggested for CD200 [49].…”
Section: Discussionsupporting
confidence: 46%
“…Circulating large and small heat shock proteins (HSP) are implicated as modulating adaptive and innate immunity in a variety of disease and inflammatory pathologies beyond their defined chaperone effects [1][2][3][4][5][6][7][8]. Large HSP are thought to act as endogenous danger signals augmenting inflammatory cytokines by triggering monocyte (MO) Toll-like receptors (TLR) and scavenger receptors independently of LPS contaminants [6,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…induces the production of cytokines that were induced by CNT exposure in previous reports (Cohen-Sfady et al, 2005;Witzmann and Monteiro-Riviere, 2006;Osterloh et al, 2007;Shvedova et al, 2007;Shvedova et al, 2008a;Shvedova et al, 2008b). Thus, our proteomics approach can detect intracellular changes with great sensitivity, which may allow us to predict slowly progressing diseases.…”
Section: Discussionmentioning
confidence: 73%
“…Another study has suggested that unlike LPS, human Hsp60 stimulates both murine macrophages and dendritic cells to secrete IFNα and neutralisation of this cytokine blocked Hsp60-induced IFNγ production by DCs. This suggests that IFNα production contributes to Hsp60-specific immune stimulation [60].…”
Section: Hsp (Chaperonin)60mentioning
confidence: 95%